The role of received social support and self-efficacy for the satisfaction of basic psychological needs in teacher education - Kassis, Wassilis; Ding, Kathrin (European journal of teacher education, 2019)
(2019). The role of received social support and self-efficacy for the satisfaction of basic psychological needs in teacher education. European Journal of Teacher Education: Vol. 42, No. 3, pp. 391-409.
Gesehen am 10.10.2019